Who Have Higher Psychological Well-Being? A Comparison Between Early Married And Adulthood Married Women - Latipun, Yuni Nurhamida, Lavina Rosalinda (Universitas Ahmad Dahlan, 2013)
AbstractTheoritically, marriage and age is two aspects related to level of psychological well-being (PWB). A person who married will be healthier physically and psychologically, so it can increase the PWB. The PWB will be higher for adult rather than younger. The question is, what about someone who got married at an early age? Is there any difference between the level of PWB on early married women and women who married in adulthood? Therefore, this study aimed to see differences between those two subjects. The research used survey methods, with PWB scale as the instrument. Subjects in this study were women aged 20-30 years, who married at the aged under 20 years and above 20 years. Subjects in this study 67 people. The results showed significant differences in levels of PWB among women who married early to married adult women (t = 3.816, p = 0.000, p <0,01). Adulthood-married women had a higher level of PWB than early age married women.Keywords: Psychological well-being, Early Marriage, adulthood marriage